CLINICAL AND DIAGNOSTIC PARAMETERS OF RHEUMATIC HEART DISEASE AND FEATURES OF THE COURSE (World Bulletin of Public Health, 2023)
In the next 15-20 years, the clinical picture of RF (rheumatic fever) has changed significantly. Most authors note an extremely low incidence of severe rheumatic carditis, a decrease in mortality and relapses of the disease, a transition to a monocindromic form of the disease, low-symptomatic and latent variants of the course, etc. American researchers note that due to the low prevalence of the disease, most doctors still do not know about complex and changing clinical picture of the disease.
Keywords: Rheumatic fever; chorea; carditis; cardiac rheumatic fever